Competition, Reputation and Compliance - Paolo Vanin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
This paper displays a linear demand oligopoly model, in which firms endogenously decide whether to enter the market and whether to specialize on high or low quality products, and then repeatedly interact to sell experience goods. It shows that the intuition that low and rising prices grant compliance with quality promises extends to this setting, provided that high quality is sufficiently important to buyers.
Keywords: L13; L14; L15; 330